Robot Motion Dynamics Modeling and Electronic Visualisation - Ramasauskas, O.; Bielskis, A. A. (Elektronika ir Elektrotechnika, 2000)
There is explains the attempt to reflect dynamics of automatically controlled robot joints in the 3D graphical environment. Since complexity to solve a nonlinear differential equations from the standpoint of robot kinematics originated a simple program tools in due form to visualize dynamics of inertial simple solids as a concentrated part of robot structure. Also presented the means of analytic research of small differential motions and shown their limited opportunities. The method and results can be used in the applied robotics design and the advanced studies of mechstronics.